The structural and functional changes of management accountants / Aliza Ramli and Suzana Sulaiman - Ramli, Aliza; Sulaiman, Suzana (Institute of Research, Development and Commercialization (IRDC), 2006)
Management accounting is regarded as an essential part in any organizational activity. Management accounting information will enable internal users to make decision effectively and contribute to the improvement ofthe efficiency and effectiveness ofexisting operation. According to International Federation ofAccountants Committee (IFAC), management accounting has evolved from focusing on cost determination and financial control to creation of value through effective use of resources. The roles of management accountants have also changed in line with the changes in management accounting techniques. Nowadays they act as the organization s internal business consultants and part of the multi-functional team. Management accounting has faced a sustained challenge in recent years as debate intensifies pver the future shape and form, which it should take. The purpose of this study was to examine Malaysian management accountants' tasks, roles, management accounting tools within a specified period - 2000 to 2004 and 2005 to 2009. The factors that drive these changes were also examined. The results provide evidence that management accountants' task, roles, management accounting tools and techniques changed overtime.